Constructing a SHIFT adherence measure (SAM): the development of a family therapy integrity measure for the SHIFT trial. Issue 2 (1st February 2016) - Masterson, Ciara; Barker, Christina; Jackson, David; Boston, Paula
Abstract : We were tasked with establishing treatment integrity for the SHIFT trial. In this article we discuss the concepts of treatment adherence and competence; arguing that the design of the trial, in particular the flexibility of the manual and the training and supervision of qualified systemic therapists, guarantees some level of treatment integrity. Despite this we decided, on the basis of a systematically informed literature review, that a post hoc evaluation of therapy tapes was in line with best practice. Our literature review found no measures that were appropriate for the needs of the trial, so we used the literature to guide our development of a SHIFT adherence measure (SAM). We outline our experience of constructing SAM in the hope of increasing transparency in this complex area of psychotherapy research. We also consider whether SAM can be transported into practice and outline future areas of research. Practitioner points: Developing measures of treatment integrity for a flexible systemic family therapy manual is a challenge but necessary for treatment to be delivered as intended. Clinicians may wish to consider whether such measures can be used in everyday practice, potentially with a role in supporting supervision or skill development.